Isolation and Screening of Antagonistic Microorganisms from Compost and Their Potential as Biological Control Agents Against for Bacterial Wilt of Tomato - Phua, Choo Kwai Hoe (2004)
Bacterial wilt caused by Ralstonia solanacearum is the most widespread and destructive disease of tomato in Malaysia. In this study, isolation and screening of microorganisms antagonistic towards R. solanacearum from composts were carried out. The effect of these antagonists on germination and growth of tomato (variety MT 11) and their effectiveness in the control of bacterial wilt were evaluated under greenhouse trials. Microorganisms were isolated from compost by using the serial dilution technique and antagonistic microorganisms were selected through the quick screening test. Results of the quick screening test showed that twelve isolates were antagonistic towards R. solanacearum. The antagonists were subsequently identified as Pseudomonas aeruginosa, Pseudomonas fluorescens, Staphylococcus saphophyticus, Pseudomonas putida biotype B, Aspergillus sp., Penicillum sp., Trichoderma sp., Brevibacterium casei and three actinomycetes, which were designated as F 141, F 178 and F 179. Antagonists were tested in dual culture assays, and for production of siderophore and volatile substances, to determine the possible mechanisms of antagonism. All the antagonists showed antibiosis against R. solanacearum in dual culture assays. In siderophore production test, all bacterial antagonists were antagonistic towards R. solanacearum on KB and KB+FeCl3. Thus, indicating that these antagonists produced antibiotics and siderophores. Strains of P. aeruginosa, P. fluorescens, S. saphophyticus, actinomycetes F178 and F 179 also produced volatile substances which, inhibited the growth of the pathogen as shown in the tests for production of volatile substances. In addition, P. aeruginosa, P. fluorescens, S. saphophyticus and Aspergillus sp. were also found to be phosphate solubilizers. These antagonists produced a clear zone on the phosphate agar plates. By using spectrophotometer and Salkowsky’s reagent, the ability of antagonists to produce Indole-3-acetic acid (IAA) was carried out. All isolates except S. saphophyticus produced varying amounts of Indole-3-acetic acid (IAA). Antagonists were bio-primed to seeds to evaluate their effect on seed germination. All antagonists except three fungal antagonists did not significantly reduce seed germination compared to the control. Fungal antagonists were therefore applied as soil drench while other antagonists were seed bio-primed in all the greenhouse experiments. The effects of antagonists applied individually on the growth of tomato plants were carried in two trials. Seeds were bio-primed with bacterial and actinomycetous antagonists while fungal antagonists were applied by drenching fungal cultures (106 cfu/ml) at seedling stage. All antagonists except for S. saphophyticus significantly increased fresh and dry weights of tomato plants compared to the control in the first greenhouse trial. In the second greenhouse trial, P. aeruginosa, P. fluorescens, S. saphophyticus and Aspergillus sp. also increased fresh and dry weights of tomato plants when planted in sandy soils containing rock phosphate. The effects of antagonists on the control of bacterial wilt were carried out in greenhouse trials. Results from application of antagonists individually to control bacterial wilt in greenhouse trial I showed that all antagonists gave significant reduction in bacterial wilt disease compared to the control. Application of P. fluorescens (B 12), P. aeruginosa (B 292) and Trichoderma sp. (F 196) individually and in combination to control bacterial wilt of tomato was carried out in greenhouse trial II. Results showed that combination treatments of B 292 and B 12; B 292 and F 196; B 12 and F 196 and B 292, B 12 and F 196 significantly reduced bacterial wilt compared to the individual treatments of antagonist. However, all the treatments were able to reduce the disease significantly compared to the control. In conclusion, these isolates were not only antagonistic towards R. solanacearum in vitro but were also able to control the disease and enhanced the growth of tomato plants. Thus, these isolates show potential as plant growth-promoters and bio-control agent for bacterial wilt.